2019
DOI: 10.1016/j.stemcr.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib Displays Atrial-Specific Toxicity in Human Stem Cell-Derived Cardiomyocytes

Abstract: Summary Ibrutinib (IB) is an oral Bruton's tyrosine kinase (BTK) inhibitor that has demonstrated benefit in B cell cancers, but is associated with a dramatic increase in atrial fibrillation (AF). We employed cell-specific differentiation protocols and optical mapping to investigate the effects of IB and other tyrosine kinase inhibitors (TKIs) on the voltage and calcium transients of atrial and ventricular human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs). IB demonstrated direct cell-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 45 publications
1
28
0
5
Order By: Relevance
“…Imaging experiments were conducted using Ca 2+ Tyrode’s solution (formulation found in Supplemental Information). The hiPSC-CMs were loaded with RH-237, blebbistatin, and Rhod-2AM sequentially before imaging as described 12,13 . Both RH-237 and Rhod-2AM were excited by 530 nm LEDs.…”
Section: Methodsmentioning
confidence: 99%
“…Imaging experiments were conducted using Ca 2+ Tyrode’s solution (formulation found in Supplemental Information). The hiPSC-CMs were loaded with RH-237, blebbistatin, and Rhod-2AM sequentially before imaging as described 12,13 . Both RH-237 and Rhod-2AM were excited by 530 nm LEDs.…”
Section: Methodsmentioning
confidence: 99%
“…The use of PSCs in the modeling of atrial arrhythmias like AF started with the discovery that properly timed retinoic acid (RA) signaling stimulates the directed differentiation of human PSCs toward the atrial cardiac lineage (148)(149)(150), resulting in CMs with mainly an AM-like AP including the presence of atriumspecific currents (e.g., I Kur and I KACh ) that could be targeted with selective ion channel modulators (151)(152)(153). Initially, these cells were used to study the hereditary components in lone AF and recently also to investigate the effects of drugs on AF susceptibility (154,155). The study by Shafaattalab and colleagues showed the Bruton's tyrosine kinase inhibitor Ibrutinib to induce pro-arrhythmic changes (i.e., APD shortening and DAD formation) in atrial-like but not in ventricular-like hESC-derived myocytes, emphasizing again the importance of using subtypespecific CMs for disease modeling (155).…”
Section: (Human) Psc-derived Atrial(-like) Cmsmentioning
confidence: 99%
“…Initially, these cells were used to study the hereditary components in lone AF and recently also to investigate the effects of drugs on AF susceptibility (154,155). The study by Shafaattalab and colleagues showed the Bruton's tyrosine kinase inhibitor Ibrutinib to induce pro-arrhythmic changes (i.e., APD shortening and DAD formation) in atrial-like but not in ventricular-like hESC-derived myocytes, emphasizing again the importance of using subtypespecific CMs for disease modeling (155). Laksman et al were the first to generate sufficient numbers of atrial-like CMs to produce multicellular sheets that could be used to study mechanisms involved in atrial arrhythmias (33).…”
Section: (Human) Psc-derived Atrial(-like) Cmsmentioning
confidence: 99%
“…Первый в классе ингибиторов ТКБ ибрутиниб используется в клинической практике для терапии ХЛЛ, однако у данного препарата отмечаются такие нежелательные явления, как кровотечения, сыпь и фибрилляция предсердий (ФП), что может быть частично связано с влиянием на другие мишени, кроме ТКБ, включая эпидермальный фактор роста и протеинтирозинкиназы семейства Tec [7][8][9].…”
Section: участники экспертного советаunclassified
“…По данным клинических исследований, применение ибрутиниба у пациентов с ХЛЛ повышает риск развития ФП, частота ФП составляла от 6 до 16% [7]. В одном из исследований был продемонстрирован специфический проаритмический эффект ибрутиниба на кардиомиоциты предсердия, который не наблюдался в рамках данного исследования у ингибитора ТКБ II поколения -акалабрутиниба за счет меньшего плейотропного эффекта [7].…”
Section: участники экспертного советаunclassified